THE STRATEGY OF THE ISLAMIC ECONOMIC SYSTEM IN INDONESIA’S DEVELOPMENT - Nissa, Izzun Khoirun (AL HUKMU: Journal of Islamic Law and Economics, 2023)
The strategy in the Islamic economic system is not an alternative economic system or an economic system middle class, but is a solutive economic system for various problems that while it appears. Research Methods used by researchers in compiling this writing is with use method descriptive . Method descriptive is method in researching something object, a system of thought or at present (Nazir, 1988:63). With this descriptive researcher try make One description, description or painting in a manner systematic , accurate about facts , attributes as well as connection between phenomena that occur in the economic system that is run. The Islamic economic system and its development in society, then For can reach balance development And well-being people, needed exists a harmonious (civilized) society, where this can be realized when there is something paradigm. The paradigm of civil society can be said to be Islamic when it is realized through principles And values Islam addressed For get fail.